Keeping Up on Geo-Everything - Moulder, Cathy (My University, 2009)
The 2009 Horizon Report on emerging technologies identifies “Geo-Everything” as a critical trend for educators in the next two to three years. How can busy professionals keep on top of these rapidly developing technologies? There is so much happening and so little time! This session will focus on tools and strategies for keeping oneself up-to-date and aware of emerging trends in neogeography, geolocative devices and just about geo-everything. The emphasis will be on achieving efficient and effective personal current awareness, with practical tips on selecting the most productive information sources and making use of web technologies to gather and winnw through the masses of journals, blogs, listservs, commercial alerts and other news sources.
Keywords: web technologies; web applications; trends; geography; higher education; Geography; Library and Information Science; Geography